ON THE TAXONOMY AND NOMENCLATURE OF SOME MECININI (COLEOPTERA, CURCULIONIDAE) - Caldara, Roberto (Fragmenta entomologica, 2008)
In accordance with the Code, ten actions are taken to preserve nomenclatural stability of names of taxa currently belonging to Mecinini. Following the provisions of ICZN Article 23.9.1, Cleopomiarus graminis (Gyllenhal, 1813) (formerly Rhynchaenus) is made a nomen protectum and Curculio ellipticus Herbst, 1795 is made a nomen oblitum; Rhinusa antirrhini (Paykull, 1800) (formerly Curculio) is made a nomen protectum and Curculio noctis herbst, 1795 is made a nomen oblitum; having met the conditions of ICZN article 75.3 the neotypes of the following taxa are designated: Curculio antirrhini Paykull, 1800, Curculio cinctus Rossi, 1790, Curculio curvirostris Rossi, 1790, Curculio linariae Panzer, 1792, Cionus thapsicola Germar, 1821, Mecinus collaris Germar, 1821. Lectotypes of Curculio ellipticus Herbst, 1795, Gymnetron eversmanni Rosenschöld, 1838, Mecinus barbarus Gyllenhal, 1838, and Mecinus longiusculus Boheman, 1845 are also designated. Rhinusa linariae (Panzer, 1792) (formerly Curculio) remains the valid name of the taxon since Curculio curvirostris Rossi, 1790 (non Fabricius, 1781 nec Herbst, 1784) is unavailable; Mecinus collaris Germar, 1821 remains the valid name of the taxon since Curculio cinctus Rossi, 1790 (non Drury, 1782 nec Geoffroy, 1785) is unavailable. The following new synonymies are proposed: Mecinus barbarus Gyllenhal, 1838 = Mecinus longiusculus Boheman, 1845 n. syn., = Mecinus teretiusculus Boheman, 1845 n. syn., = Mecinus filiformis Aubé, 1850 n. syn.; Rhinusa florum (Rübsaamen, 1895) = Gymnetron smreczynskii Fremuth, 1972 n. syn.; Rhinusa tetra (Fabricius, 1792) = Cionus thapsicola Germar, 1821 n. syn. Rhinusa eversmanni (Rosenschöld, 1838) is the name proposed for Rhinusa thapsicola sensu auctorum (non Germar, 1821).